Drivers of academic engagement and university-industry collaboration in conditions of Slovakia - Michal Hrivnák; Jana Jarábková (Administrative Sciences, 2022)
Universities have been perceived for several decades as an important development factor in the space that shapes the regional environment throughout the generation of new knowledge or technologies and the production of human capital. Our paper focuses on the less researched phenomenon of academic engagement, and thus, the development of university knowledge transfer based on interpersonal links between researchers and application actors from an academic perspective. This empirical study evaluates the results of a nationwide survey of academic researchers devoted to unhiding various aspects of formal and informal cooperation on an interpersonal basis. Using an econometric approach, the study investigates determinants of academic engagement of individual researchers and describes patterns of formal and informal ties between academics and businesses. The results explain which researchers participate in academic engagement activities and elaborate on the motivations and barriers of university-industry cooperation at the level of the individual. We also identified a significant volume of informal dissemination of knowledge of universities in the space via various channels.
Keywords: 350; academic engagement; knowledge diffusion; university; university-industry collaboration